Histopathological Study of Hysterectomy Operations in A University Clinic in Tehran From 2005 to 2009 - Mahmoud Khaniki; Mahsa Shojaie; Azam Tarafdari (Tehran University of Medical Sciences, 2011)
Objective: We intended to determine causes and histological pattern of hysterectomies in an Iranian population. Materials and methods: Archived reports of pathology department of a university hospital dated March 2005 to March 2009 were retrospectively reviewed. Age, chief complaint, type of operation including abdominal, vaginal and subtotal hysterectomy, the indication of the operation and the pathology of the specimen were retrieved from the records. Results: The average rate of hysterectomy was 219 per year. The average age of the patients was 49.6±11.3. About 40% of cases aged 45-54 years. The main chief compliant was abnormal uterine bleeding (62.2%). The leading preoperative indication for hysterectomy operations were uterine leiomyoma (24.8%) and then abnormal uterine bleeding and abdominal/pelvic mass. The most frequent pathologic findings were leiomyoma (22.0%) and adenomyosis (12.1%). In 11.8% of hysterectomy specimens no pathologic lesion was found. Conclusion: The hysterectomy is rather common in Iran with age dependent pattern of indications and corresponding pathologies.